Importance of big data - Ansari, S. (IGI Global, 2015)
Combining vast amounts of heterogeneous data and increasing the processing power of existing database management tools is no doubt the emerging need of IT industry in coming years. The complexity and size of data sets that need to be acquired, analyzed, stored, sorted or transferred has spiked in the recent years. Due to the tremendously increasing volume of multiple data types, creating Big Data applications that can extract the valuable trends and relationships required for further processes or deriving useful results is quite challenging task. Companies, corporate organizations or be it government agencies, all need to analyze and execute Big Data implementation to pave new paths of productivity and innovation. This chapter discusses the emerging technology of modern era: Big Data with detailed description of the three V's (Variety, Velocity and Volume). Further chapters will enable to understand the concepts of data mining and big data analysis, Potentials of Big Data in five domains i.e. Healthcare, Public sector, Retail, Manufacturing and Personal location Data. Â© 2015, IGI Global. All rights reserved.